2012
DOI: 10.1007/s00253-012-4519-9
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of microorganisms with rare earth ions and their utilization for separation and environmental technology

Abstract: In recent years, rare earth elements (REEs) have been widely used in various modern technological devices, and the global demand for REE has been increasing. The increased demand for REEs has led to environmental exposure or water pollution from rare earth metal mines and various commercial products. Therefore, the development of a safe technology for the separation and adsorption of REEs is very important from the perspective of green chemistry and environmental pollution. In this review, the application and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 54 publications
3
66
0
Order By: Relevance
“…The loss of LtaS activity in B. subtilis impacts cell division, cell morphogenesis, and divalent cation homeostasis (6). In addition to these phenotypes, a quadruple ltaS homolog mutant shows a loss of LTA (7), an aberrant twisted morphology, slower growth (6), and reduced adsorption of rare earth elements (8,9). Moreover, we reported that D -dependent transcription of lytF, which encodes a DL-endopeptidase that functions in cell separation, is reduced in an ltaS mutant and is nearly absent in multiple mutants of ltaS and its homologs (10).…”
mentioning
confidence: 99%
“…The loss of LtaS activity in B. subtilis impacts cell division, cell morphogenesis, and divalent cation homeostasis (6). In addition to these phenotypes, a quadruple ltaS homolog mutant shows a loss of LTA (7), an aberrant twisted morphology, slower growth (6), and reduced adsorption of rare earth elements (8,9). Moreover, we reported that D -dependent transcription of lytF, which encodes a DL-endopeptidase that functions in cell separation, is reduced in an ltaS mutant and is nearly absent in multiple mutants of ltaS and its homologs (10).…”
mentioning
confidence: 99%
“…Naturally-occurring microbes can sorb a variety of PGMs, REEs and heavy metals, including Pt, Fe, Ni, Cu, Zn, Pb, Cu, Pd, Ag, Cd, Pt, Au, and Hg, with binding capacities typically on the order of 10 −5 to 10 −3 mol metal g −1 (dry wt) microbe (e.g., [4446]). Thus, on a dry weight basis, the metal binding capacities of microbes compare favorably to the binding capacities of commercial ion exchangers.…”
Section: Microbe-metal Interactionsmentioning
confidence: 99%
“…Thus, on a dry weight basis, the metal binding capacities of microbes compare favorably to the binding capacities of commercial ion exchangers. Biosorption of metals to microbes can involve a variety of processes, including absorption, ion exchange, complexation, and precipitation [45,46]. These processes are critically regulated by the chemical groups displayed on the extracellular surfaces of microbial cells, such as carboxyl, phosphoryl, hydroxyl, carbonyl, and thiol moities.…”
Section: Microbe-metal Interactionsmentioning
confidence: 99%
“…Naturally The metals biosorption to microbes can involve a variety of processes, including absorption, ion exchange, complexation, and precipitation [15,16]. These processes are determined by the chemical groups displayed on the extracellular surfaces of microbial cells, such as carboxyl, phosphoryl, hydroxyl and carbonyl.…”
Section: Why Bio-processes?mentioning
confidence: 99%